Features of Human Decidual NK Cells in Healthy Pregnancy and During Viral Infection - Jabrane-Ferrat, Nabila (Frontiers in Immunology, 2019)
The hallmark of human early pregnancy is the accumulation of a unique population of Natural Killer (dNK) cells at the main maternal-fetal interface, the decidua basalis. dNK cells play a crucial role in successful placentation probably by orchestrating the invasion of trophoblast cells deep into the decidua basalis and remodeling of the maternal spiral arteries. Recent advances in the field emphasize the importance of the local microenvironment in shaping both the phenotype and the effector functions of these innate lymphoid cells. Despite slow progress in the field, ex vivo studies revealed that dNK cells sense and destroy infected cells in order to protect the fetus from invading pathogens. In this review, we will discuss key features of dNK cells during healthy pregnancy as well as their functional adaptations in limiting pathogen dissemination to the growing conceptus. The challenge is to better understand the plasticity of dNK cells in the maternal-fetal interface. Such insights would enable greater understanding of the pathogenesis in congenital infections and pregnancy disorders.